Seni motif cap pada kain bagi penderita psikotik di Dinas Sosial Meruya Unit Informasi (UILS Meruya) - Nina Maftukha (Universitas Pendidikan Indonesia (UPI), 2021)
The art of this stamp motif has been known since prehistoric times, and the results can be seen in Leangleang Cave, Kalimantan and Altamira Cave, Australia. The stamp technique is very simple and can take advantage of objects and plants in the environment around us. Based on the survey, there are no products in the form of fashion fabric for the cultivating activities at the Social Service Information Unit (UILS) Meruya. Therefore, this service carries the theme of stamped art on cloth. Stamp is one of the simplest graphic arts or printing techniques, namely the stamp motif on the fabric that is created with the texture of various types of leaves in the surrounding environment. For example, we can take advantage of the texture of the banana midrib bone with a certain composition and pattern. The target to be achieved is to introduce Meruya's Social Service Information Unit (UILS) to people. The application is by applying the motif to the fabric. This can train the cognitive and motor aspects of students. The implementation methods are (1) introducing the technique of making stamps from banana midribs, (2) applying the motif to the fabric, (3) creating unique compositions and patterns of motifs, (4) practicing making motifs with stamp coloring techniques, (4) making creative economy products in the form of fashion products.